STUDI TENTANG MINAT BELI ULANG PRODUK TUPPERWARE DI KOTA PEKALONGAN - Purnama Sari, Putri Intan (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2016)
The purpose of this research are to analyze the influence of Corporate’s Images and the satisfaction of customers against the brand to rise the customer’s repurchase intentions. The research’s object which do in this case, are the Tupperware’s Customers in Pekalongan City, who does bought Tupperware’s products with minimal twice purchasing, and the segmentation are 20 years old buyers. Purposive sampling technic are use in this research . There are 120 respondens that according to the minimum sample size rules on the fourth construct’s variable.The data analyze technic which used in this case istheStructural Equation Model (SEM) dari software AMOS 21.The model’s that proposed in this research’s case can be accepted after fulfill the assumptions of normality and Standardized Residual Covariance ±2,58and the value of Determinant ofSample Covariance with the Matrix’s results are5,597.The results from SEM’s analyze to fulfill the model’s criteria of Goodness of Fit – Full Model are chi square = 52,199; CMIN/DF = 1,065; probability = 0,351; GFI = 0,937; AGFI = 0,900; TLI = 0,994; CFI = 0,995; RMSEA = 0,023.The results of this modelscan be use in this research case.The results from the fourth hypothesisis provethe existingof therejected hypothesis. According to the results of this research,we can take the conclusion that thecorporation’s images can increase the brand trustment and the repurchase intentions. Otherwise from it, the customer’s satisfaction can increase the repurchase intentions. Mean while thecustomer’s satisfactionscan’tto influent the brand trustment. According to this research, there are a fewlimitation oh this research and the upcoming research’s agenda that can be done in the next research.